Direct Oral Anticoagulants: From Randomized Clinical Trials to Real-World Clinical Practice - Roberti, Roberta; Iannone, Luigi Francesco; Palleria, Caterina; Curcio, Antonio; Rossi, Marco; Sciacqua, Angela; Armentaro, Giuseppe; Vero, Ada; Manti, Antonia; Cassano, Velia; Russo, Emilio; De Sarro, Giovambattista; et al. (Frontiers in Pharmacology, 2021)
Direct oral anticoagulants (DOACs) are a more manageable alternative compared with vitamin K antagonists (VKAs) to prevent stroke in patients with non-valvular atrial fibrillation and to prevent and treat venous thromboembolism. Although their widespread use in clinical practice, there are still some unresolved issues on optimizing their use in particular clinical settings. Herein, we reviewed the current clinical evidence on uses of DOACs from pharmacology and clinical indications to safety and practical issues such as drugs and food interactions. Dabigatran is the DOACs most affected by interactions with drugs and food, although all DOACs demonstrate a favorable pharmacokinetic profile. Management issues associated with perioperative procedures, bleeding treatment and special populations (pregnancy, renal and hepatic impairment, elderly, oncologic patients) have been discussed. Literature evidence shows that DOACs are at least as effective as VKAs, with a favorable safety profile; data are particularly encouraging in using edoxaban low doses in elderly patients, and edoxaban and rivaroxaban in the treatment of venous thromboembolism in oncologic patients. In the next year, DOACs clinical indications are likely to be further extended.